Mechanical properties of hybrid lignocellulosic fiber‑reinforced biopolymer green composites: a review - Muhammad Asyraf, Muhammad Rizal; Syamsir, Agusril; Ishak, Mohamad Ridzwan; Mohd Sapuan, Salit; Mohd Nurazzi, Norizan; Norrrahim, Mohd Nor Faiz; Ahmad Ilyas, Rushdan; Khan, Tabrej; Abd Rashid, Mohamad Zakir (Springer - Korean Fibers Society, 2023)
Sustainability has been a global awareness due to the serious reduction of synthetic materials, especially petroleum. Many sectors and researchers have shifted toward lignocellulosic fibers from biomass wastes to replace synthetic fibers and reinforced bio-based polymer composites. The shift in composite landscape toward green composites is due to their availability, low carbon emission, and biodegradability. Generally, green composites can be hybridized with various lignocellulosic fibers and they have high potential in the civil and automotive fields due to their mechanical performance. Nevertheless, research has found that they have inappropriate matches for the unique material attributes of green composites even though many studies have covered this topic. Studies on the mechanical performance of hybrid natural fibers green composites are still very limited. Overall, there are various mechanical properties of hybrid lignocellulosic fibers depending on their physical properties, orientation and sequence, treatments, polymers, and fabrication methods. From these considerations, a series of matching application properties are explained: these include structural applications for many industries. Thus, this review article establishes critical discussions on the mechanical properties of hybrid natural fibers reinforced biopolymer green composites. Some studies have identified the research gaps and deduced that the potential applications of hybrid green composites have not been explored.